2020
DOI: 10.2147/jpr.s234761
|View full text |Cite
|
Sign up to set email alerts
|

<p>Acupotomy versus Manual Acupuncture for the Treatment of Back and/or Leg Pain in Patients with Lumbar Disc Herniation: A Multicenter, Randomized, Controlled, Assessor-Blinded Clinical Trial</p>

Abstract: Background: Acupotomy, which involves the addition of a scalpel function to the conventional acupuncture treatment, has recently been applied as a conservative treatment method for lumbar disc herniation (LDH). This study investigated the effectiveness and safety of acupotomy, compared to manual acupuncture, for the treatment of patients with LDH. Methods: A total of 146 patients diagnosed with LDH were randomly assigned to either the acupotomy group or the manual acupuncture group at a 1:1 ratio. Participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…Using our inclusion criteria, no studies on dry needling were identified cluded studies (n = 10) used acupuncture for treatment of sciatica and are out bles 3 and 4. The inclusion criteria for patients with sciatica varied across the s studies included participants with sciatica symptoms and clinical findings tha with MRI or CT confirmation of lumbar disc herniation [22,[38][39][40][41]. Three stud patients with a clinical diagnosis of sciatica based on nerve root pain and re [24,42,43].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Using our inclusion criteria, no studies on dry needling were identified cluded studies (n = 10) used acupuncture for treatment of sciatica and are out bles 3 and 4. The inclusion criteria for patients with sciatica varied across the s studies included participants with sciatica symptoms and clinical findings tha with MRI or CT confirmation of lumbar disc herniation [22,[38][39][40][41]. Three stud patients with a clinical diagnosis of sciatica based on nerve root pain and re [24,42,43].…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, at week 28 follow-up only the EA group showed significantly decreased leg pain compared to the baseline, implying that the effect of EA but not electrotherapy lasted for 28 weeks. Jeong et al reported that acupuncture led to reductions in pain of 8.13 and 12.28 mm on the VAS at 4 and 6 weeks from baseline, respectively, in 70 patients with radicular symptoms consistent with lumbar disc herniation [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 19 , 20 ] Acupotomy is a special technique of acupuncture conducting minimally invasive surgery using a needle with a flat blade shape and causes natural opioid-mediated pain suppression by stimulating local alpha–delta nerve fibers. [ 21 , 22 ] Fire-needling acupuncture is an acupuncture technique that inserts a heated acupuncture needle on the body to add cauterization effect, and it promotes microcirculation in the treated area through the regulation of cutaneous nerves, which is beneficial for the absorption of inflammatory metabolites. [ 23 ] Because various types of acupuncture are used for the treatment of gouty arthritis based on these mechanisms, additional analyses of each technique are required along with analysis of the entire acupuncture treatment.…”
Section: Discussionmentioning
confidence: 99%